Dr. Luis Dao Lameh first report of congenital Chagas (Revista Venezolana de Salud Pública, 2018)
It briefly describes the scientific achievements of Dr. Luis Dao, emphasizing the description of the first global report congenital transmission of Trypanosoma cruzi and Chagas disease, occurred in Guárico State, Venezuela.
Keywords: Transmission; congenital; Chagas; Venezuela; NaWarao